Deregulation of Polycomb Repressive Complex-2 in Mantle Cell Lymphoma Confers Growth Advantage by Epigenetic Suppression of cdkn2b - Demosthenous, Christos; Gupta, Shiv K.; Sun, Jing; Wang, Yongsen; Troska, Tammy P.; Gupta, Mamta (Frontiers in Oncology, 2020)
The polycomb repressive complex 2 (PRC2) maintains the transcriptional repression of target genes through its catalytic component enhancer of zeste homolog 2 (EZH2). Through modulating critical gene expression, EZH2 also plays a role in cancer development and progression by promoting cancer cell survival and invasion. Mutations in EZH2, are prevalent in certain B-cell lymphoma subtypes such as diffuse large cell lymphoma and follicular lymphoma; while EZH2 mutations are not reported in the mantle cell lymphoma (MCL). Here we demonstrate that the PRC2 components EZH2, EED and SUZ12 is upregulated in the MCL cells as compared to normal B-cells regardless of EZH2 mutations. Moreover, cells stably transfected with wild-type EZH2 or-EED showed increased H3K27-trimehtylation and cell growth. However, unlike wild-type EZH2, ectopic expression of a deletion construct of EZH2 (EZH2Δ315-738 lacking SET domain) had no growth advantage over control cells. Pharmacological inhibition of EZH2 suppressed H3K27-trimethylation and had significant inhibitory effect on cell growth and colony forming capacity (p< 0.05) of MCL cells, and this effect was more or less comparable to anti-proliferative effects of EZH2 inhibition seen in cells harboring EZH2-mutation. Mechanistically, EZH2 appears to downregulate expression of cdkn2b gene by enhancing H3K27-trimethylation, suppressive epigenetic mark, at the cdkn2b promoter region. Overall, these results suggest that deregulation of PRC2 in MCL is associated with epigenetic suppression of cdkn2b, and in part responsible for increased cell growth in an EZH2 dependent